Devolution in the Italian Healthcare System. The Role of Regions in Organizing Healthcare after 2001 - Monika Urbaniak (Barometr Regionalny)
A very important act reforming healthcare in Italy was the Act of 23 December 1978, which initiated devolution of competence in the matter of healthcare, with the transfer of administrative and legislative functions in this field to regions. As a result of this reform, Italy underwent a transfer from the insurance model of healthcare financing to the model of national healthcare service. Other changes concerning, first of all, the form of the regional state and broadening regional autonomy were introduced by the Constitutional Act No. 3 of 18 October 2001, amending Title V of the Constitution and concerning the status of regions, provinces and communes. As a result of these reforms, it is regions that currently represent the most important level of administration between the central government and communes. The main result of the process of federalism is how the regions were granted authority to allocate owned funds in the healthcare system in the manner that they consider most appropriate for funding basic levels of services (LEA) in their territory, as well as the management of the organization of healthcare in their local area in the way that meets the requirements of the population living there.